(untitled) (El-Wahat Journal for Research and Studies, 2023)
Abstract Nowadays, Economic Institutions Are Regarded As The Primary Engine Of Economies As They Can Provide The Social And Economic Foundation For Societies, And Human Resources Are One Of Their Most Important Assets. Cultivating Its Productive Capacity Is What The Human Resources Department Intends To Do Via Set Vocational Training Policies And Programs That Attempt To Enhance Individuals’ Abilities, And Technical And Management Skills, As Well As To Assure Its Continuity And Achievement Of Its Intended AnضD Established Goals. Keywords: Human Resources Management, Human Resources, Vocational Training